Downregulation of monocyte miRNAs: implications for immune dysfunction and disease severity in drug-resistant tuberculosis - Sampath, Pavithra; Moorthy, Manju; Menon, Athul; Madhav, Lekshmi; Janaki, Aishwarya; Dhanapal, Madhavan; Natarajan, Alangudi Palaniappan; Hissar, Syed; Ranganathan, Uma Devi; Ramaswamy, Gopalakrishna; Bethunaickan, Ramalingam (Frontiers in Immunology, 2023)
Background: Monocyte miRNAs govern both protective and pathological responses during tuberculosis through their differential expression and emerged as potent target for biomarker discovery and host-directed therapeutics. Thus, our profound interest is to look at the miRNA profile of sorted monocytes across TB disease spectrum (drug-resistance TB (DR-TB), drug-sensitive TB (DS-TB) and latent TB) and healthy individuals (HC) to understand the underlying pathophysiology and their regulatory mechanism. Methods: We sorted total monocytes including all three subsets (HLA-DR+CD14+, HLA-DR+CD14+CD16+, and HLA-DR+CD16+cells) from PBMCs of healthy and TB infected individuals through flow cytometry and subjected to Nanostring based miRNA profiling. Results: The outcome was the differential expression of 107 miRNAs particularly the downregulation of miRNAs in active TB groups (both drug-resistance and drug-sensitive). The miRNA profile revealed differential expression signatures: i) decline of miR-548m in DR-TB alone, ii) decline of miR-486-3p in active TB but significant elevation only in LTB iii) elevation of miR-132-3p only in active TB (DR-TB and DS-TB) and iv) elevation of miR-150-5p in DR-TB alone. The directionality of functions mediated by monocyte miRNAs from Gene Set Enrichment Analysis (GSEA) facilitated two phenomenal findings such as i) bidirectional response between active disease (activation profile in DR-TB and DS-TB compared to LTB and HC) and latent infection (suppression profile in LTB vs HC) and ii) hyper immune activation in DR-TB group compared to DS-TB. Conclusion: Thus, monocyte miRNA signatures provide a pathological clue for the altered monocyte function, drug-resistance and disease severity. Further studies on monocyte miRNAs may shed light on the immune regulatory mechanism for tuberculosis.